Puerperal Complications in a Tertiary Hospital - Rijal, Hima; Maskey, Suvana (Nepal Medical College Journal, 2021)
Postnatal period is considered as an important part in reproductive life of women. Even though the antenatal phase and labour are utmost important, puerperal phase of pregnancy cannot be overlooked. Puerperal complication can sometime lead to diabilities for lifelong of women. For the prevention of postnatal complication, antenatal prepadareness is needed. The objective of this study was to find out the incidence of puerperal complications and associated risk factors. This is a retrospective, descriptive study conducted at Tribhuvan University Teaching Hospital, Department of Obstetrics and Gynaecology from April 2019 to March 2020. The cases of puerperal complications were noted from the record book from ward. The individual files were collected from record section. Data was collected from record files and analysed. Total number of deliveries were 4932 in one year. Out of which, 84 cases (1.7%) were admitted due to various puerperal complications. Majority of the women admitted with puerperal complications were between 21-29 years, 59.5%. Sixty-four percent (n=54) were primipara and 35.7%(n=30) were multipara. Seventy-six (90.5%) were term deliveries, 6(7%) were preterm and 2(2.4%) were post term deliveries. Sixty-two (74%) had emergency cesarean section as mode of delivery. Major indication of emergency cesarean section was fetal distress (29.8%, n=25). Surgical site infection (53/84,63%) was the commonest puerperal complication followed by puerperal sepsis (8/84,9.5%). Fifty- three cases of surgical site infection (SSI) were observed in patients who had undergone emergency cesarean section. Associated medical condition like hypertension, diabeties, anemia, obesity was seen in 33.5% (n=33) of the cases. Surgical Site Infection is the most common puerperal complication and commonly seen in women who had undergone emergency cesarean section.